SUSTAINABLE TOURISM POTENTIAL FOR THE PALAUNG ETHNIC GROUP AT THE ANG KHANG ROYAL PROJECT - CHAICHOMPOO, CHALERMCHAI (ASEAN Journal on Hospitality and Tourism, 2011)
The objectives of this investigation are to examine the potential for sustainable tourism for the Palaung ethnic group at Nor Lae Village, Chiang Mai, Thailand and to propose guidelines for making tourism for the group sustainable. The potential for tourism for the ethnic group includes its ethnic identity, hand-woven textiles, traditional music and dance, and organic farming produce. Firstly, classified under the MonKhmer language group, the Paluang remain distinct linguistically and culturally. Secondly, the ethnic textiles are hand-woven, using back-strapped looms, and natural dyes from plants are used in order to preserve its folk wisdom and the environment. Thirdly, Palaung traditional music and dance are unique and exotic. A music and dance group has been formed and has performed locally and nationally with the aim of maintaining its cultural heritage. Finally, products from organic farming have been produced with the full support of the royal project, including temperate vegetables, fruits, flowers and tea; and attracting a large number of tourists to the area.